Nanotechnological Advances for Nose to Brain Delivery of Therapeutics to Improve the Parkinson Therapy - Khatri, Dharmendra K.; Preeti, Kumari; Tonape, Shivraj; Bhattacharjee, Sheoshree; Patel, Monica; Shah, Saurabh; Singh, Pankaj K.; Srivastava, Saurabh; Gugulothu, Dalapathi; Vora, Lalitkumar; Singh, Shashi B. (Current Neuropharmacology, 2023)
Blood-Brain Barrier (BBB) acts as a highly impermeable barrier, presenting an impediment to the crossing of most classical drugs targeted for neurodegenerative diseases including Parkinson's disease (PD). About the nature of drugs and other potential molecules, they impose unavoidable doserestricted limitations eventually leading to the failure of therapy. However, many advancements in formulation technology and modification of delivery approaches have been successful in delivering the drug to the brain in the therapeutic window. The nose to the brain (N2B) drug delivery employing the nanoformulation, is one such emerging delivery approach, overcoming both classical drug formulation and delivery-associated limitations. This latter approach offers increased bioavailability, greater patient acceptance, lesser metabolic degradation of drugs, circumvention of BBB, ample drug loading along with the controlled release of the drugs. In N2B delivery, the intranasal (IN) route carries therapeutics firstly into the nasal cavity followed by the brain through olfactory and trigeminal nerve connections linked with nasal mucosa. The N2B delivery approach is being explored for delivering other biologicals like neuropeptides and mitochondria. Meanwhile, this N2B delivery system is associated with critical challenges consisting of mucociliary clearance, degradation by enzymes, and drug translocations by efflux mechanisms. These challenges finally culminated in the development of suitable surfacemodified nano-carriers and Focused- Ultrasound-Assisted IN as FUS-IN technique which has expanded the horizons of N2B drug delivery. Hence, nanotechnology, in collaboration with advances in the IN route of drug administration, has a diversified approach for treating PD. The present review discusses the physiology and limitation of IN delivery along with current advances in nanocarrier and technical development assisting N2B drug delivery.
Keywords: nano drug delivery